MAZHAB GOOGLE: Nalar Fikih Generasi Z dan Fatwa Shopping di SMAN 2 Lamongan dan MA “Matholi’ul Anwar” Lamongan - Abdulloh Faqih (TA'LIM : Jurnal Studi Pendidikan Islam, 2023)
This research is motivated by the phenomenon of the presence of the internet era which is accompanied by the increasingly massive penetration of social media in various aspects of life so that the emergence of adherents of the Google school is the mainstream way of understanding Islam for the current generation Z. The research method uses a qualitative approach with a multi-site study type of research. The data collection technique used was observation, in-depth interviews and documentation of Generation Z who were at MA "Matholi'ul Anwar" Lamongan and SMAN 2 Lamongan who have the same characteristics from January to December 2021. While checking the validity of the data by using credibility, transferability, dependability, and confirmability. The research findings show that; There has been a shift among Generation Z who are digital natives or native speakers of digital technology, so they prefer to use "Google" in finding answers and understanding fiqh rather than reading and asking teachers for reasons of more privacy, effectiveness and efficiency.